PENETAPAN SYARAT DALAM AKAD PERNIAGAAN: KEDUDUKAN DAN GARIS PANDUANNYA MENURUT FIQH ISLAM - Abdullah, Atikullah (Jurnal Syariah, 2019)
The validity of the stipulation of shurut, conditions in business contracts is a point of lengthy discussion among fuqaha’, Islamic law scholars in the past and at present. Despite of the numbers of disagreements, they all agree that justice or in this particular issue, contractual justice must prevail. Therefore, the disagreement among the scholars can be summed up to the diasagreement about the way how justice to all contracting parties can be best protected and the interest of the society can be best served. Identifying the above mentioned question, is the main objective of this paper. To achieve this, this paper will investigate the views of fuqaha’ on some related issues like the theory of freedom of contract and ibahat al-asl. The finding shows that as long as the shurut do not contradict any of the contractual principles laid down in the nusus of the Qur’an and the prophetic hadith, do not endanger the interest of the contracting parties in particular and the interest of society in general and the shurut are also well accepted by the society as good for them, than it must be so considered and be regarded as legally valid.